Polypharmacy and Polymorbidity in Older Adults in Brazil: a public health challenge - Ramos, Luiz Roberto (Rev Saude Publica, 2016)
OBJECTIVE: To analyze variations in the prevalence of chronic use of medicines by older adults in Brazil according to its possible association with the most prevalent chronic diseases and demographic and health factors, and to identify risk factors for polypharmacy. METHODS: A study based on data from the National Survey on Access, Use and Promotion of Rational Use of Medicines (PNAUM), a cross-sectional, population-based survey with probability sampling in Brazilian urban areas. The independent variable was the number of chronic-use medicines taken by older adults, linked to eight chronic diseases investigated. The intervening variables were gender, age group, marital status, level of education, socioeconomic status, Brazilian region, body mass index, smoking, self-perceived health, hospitalization in the previous year and having health insurance, besides the investigated chronic diseases. A multivariable analysis identified risk factors for polypharmacy. RESULTS: Prevalence of at least one chronic-use medicines among older adults was 93.0%. Of the total number of older adults, 18.0% used at least five medications (polypharmacy). Polypharmacy was higher among the oldest individuals (20.0%), in the South region (25.0%), in those with poor self-perceived health (35.0%), in obese individuals (26.0%), in those with reported health insurance (23.0%) or hospitalization in the previous year (31.0%), and among those who reported any of the investigated diseases, particularly diabetes (36.0%) and heart diseases (43.0%). The variables remaining in the final risk model for polypharmacy were age, region, perceived health, health insurance, hospitalization in the previous year and all investigated diseases except stroke. CONCLUSIONS: Older adults with specific diseases have risk factors for polypharmacy modifiable by actions aimed at the rational use of medicines. With the current population aging and successful drug access policy, the trend is an increase in drug use by older adults, which should feature as a priority in the planning agenda of the Brazilian Unified Health System (SUS).